Beta-Defensin 2 and 3 Promote Bacterial Clearance of Pseudomonas aeruginosa by Inhibiting Macrophage Autophagy through Downregulation of Early Growth Response Gene-1 and c-FOS - Wu, Yongjian; Li, Dandan; Wang, Yi; Liu, Xi; Zhang, Yuanqing; Qu, Wenting; Chen, Kang; Francisco, Ngiambudulu M.; Feng, Lianqiang; Huang, Xi; Wu, Minhao (Frontiers in Immunology, 2018)
Beta-defensins 2 and 3 (BD2 and BD3) are inducible peptides present at the sites of infection, and they are well characterized for their antimicrobial activities and immune-regulatory functions. However, no study has thoroughly investigated their immunomodulatory effects on macrophage-mediated immune responses against Pseudomonas aeruginosa (PA). Here, we demonstrate that BD2 and BD3 suppressed macrophage autophagy but enhanced the engulfment of PA and Zymosan bioparticles as well as the formation of phagolysosomes, using immunofluorescence staining and confocal microscopy. Plate count assay showed that macrophage-mediated phagocytosis and intracellular killing of PA were promoted by BD2 and BD3. Furthermore, microarray and real-time PCR showed that the expression of two genes, EGR1 and c-FOS, was attenuated by BD2 and BD3. Western blot revealed that BD2 and BD3 inhibited the translocation of EGR1 and c-FOS into the nucleus. Knockdown of EGR1 and c-FOS by siRNA transfection suppressed macrophage autophagy before and after PA infection; while over-expression of these two transcription factors enhanced autophagy but reversed the role of BD2 and BD3 on macrophage-mediated PA eradication. Together, these results demonstrate a novel immune defense activity of BD2 and BD3, which promotes clearance of PA by inhibiting macrophage autophagy through down-regulation of EGR1 and c-FOS.